HGG-27. CLINICAL ANALYSIS OF CHOROID PLEXUS TUMORS. (23rd April 2019) - Nakano, Yoshiko; Saito, Ryuta; Kanamori, Masahiro; Kawamura, Atsushi; Nakamura, Taishi; Watanabe, Yuko; Matsusaka, Yasuhiro; Kunihiro, Noritsugu; Okada, Keiko; Hara, Junichi; Sakamoto, Hiroaki; Ichimura, Koichi
Abstract: BACKGROUND: Choroid plexus tumors (CPT) includes choroid plexus papilloma (CPP), atypical choroid plexus papilloma (aCPP), and choroid plexus carcinoma (CPC). Because of its rarity, limited data are available on the current status of treatment and outcomes for pediatric CPTs. METHOD: Clinical data on patients with CPT aged between 0 and 30 years at diagnosis treated in 4 institutions in Japan were retrospectively reviewed. RESULTS: Twenty-seven pts were pathologically diagnosed with CPT. One individual who was initially diagnosed with CPC developed a rhabdoid tumor of the kidney, and the diagnosis was changed to AT/RT. The remaining 26 pts were further analyzed. Median age at diagnosis was 1 year (0 to 25). The mean follow-up period was 8.1 years (range: 0.2 to 24 years). All pts with CPP (n=11) underwent gross-total resection without adjuvant therapy, and none of them experienced relapse. Of the 7 pts with aCPP, 3 experienced relapse. Two pts with local relapse were alive after salvage surgery, while one pt died of the disseminated disease. Regarding pts with CPC (n=8), 7 pts received surgery followed by adjuvant chemotherapy and radiotherapy. Two pts survived without evidence of disease. Six pts relapsed, three of whom died with disseminated disease and the other three achieved remission without dissemination. OS and EFS of CPC pts at 10 years were 58% and 15%, respectively. Two patients were diagnosed with Li-Fraumeni syndrome (LFS). One LFS patient with CPC was alive with a follow-up of three years and the other was died of medulloblastoma after complete remission of aCPP. CONCLUSION: Compared with the excellent prognosis of CPP, the survival rates for CPC and aCPP are unsatisfactory. Molecular analysis to correlate with clinical data is underway. IMMUNOLOGY/IMMUNOTHERAPY